COMBINING THE MAGIC OF ARTIFICIAL INTELLIGENCE (AI) IN CULTURAL WISDOM - Suryani, Ita; Marta, Rustono Farady; Wijaya, Beby Chandra; Romaria, Gustina; Engliana, Engliana (ASPIRATION Journal, 2024)
In the modern era dominated by technological advancements, artificial intelligence (AI) has become an extraordinary phenomenon. The effort to utilize technological advances to preserve, develop, and honor cultural heritage is known as combining the magic of artificial intelligence with cultural wisdom. The purpose of this study is to find out how artificial intelligence (AI), with its unique capabilities and technology, is an effective tool to maintain, promote, and enrich cultural wisdom. The case study methodology, combined with the qualitative approach, is used in this study. The conclusion of this study suggests using a case study methodology combined with an iterative process. The results show that through advanced technology, artificial intelligence (AI) helps maintain language, literature, art, music, and the natural environment with cultural value. Keywords: Artificial Intelligence, Local Wisdom